Inequity in the use of physician services in Norway before and after introducing patient lists in primary care - Monstad Karin; Grasdal Astrid L (BMC, 2011)
Abstract Background Inequity in use of physician services has been detected even within health care systems with universal coverage of the population through public insurance schemes. In this study we analyse and compare inequity in use of physician visits (GP and specialists) in Norway based on data from the Surveys of Living Conditions for the years 2000, 2002 and 2005. A patient list system was introduced for GPs in 2001 to improve GP accessibility, strengthen the stability of the patient-doctor relationship and ensure equity in the use of health care services for the entire population. Method We measure horizontal inequity by concentration indices and investigate changes in inequity over time when decomposing the concentration indices into the contribution of its determinants. Results We find that pro-rich inequity in the probability of seeing a private outpatient specialist has declined, but still existed in 2005. Conclusion Improved patient-doctor stability as well as better GP accessibility facilitated by the introduction of patient lists improved access to private specialist services. In particular the less well off benefited from this reform.